C*-algebras over arens algebras - Bekbaev, Dilmurad; Ganiev, Inomjon (American Institute of Physics, 2015)
A class of Arens algebras of sections are considered. It is shown that such slgebras are C*-algebras over Arens algebras and these C*-algebras are complete locally convex metrizable algebras.